Prospective evaluation of drug–drug interactions in ambulatory cancer patients initiated on prophylactic anticoagulation. (October 2020) - Ng, Hank K; Rogala, Britny G; Ades, Steven; Schwartz, Joanna R; Ashikaga, Takamaru; Vacek, Pamela; Holmes, Chris E
Introduction: Drug options for VTE prophylaxis are increasing for ambulatory cancer patients and data regarding anticoagulant-drug interactions and their relationship to VTE and bleeding are needed to improve care. Methods: Over one year, 108 cancer patients with high VTE risk were prospectively identified. Potential anticoagulant-drug interactions were ascertained by chart review and graded on need for intervention. Providers selected anticoagulant prophylaxis based on potential drug interactions and patient-provider discussion. A cross-sectional analysis was performed thereafter to evaluate VTE and bleeding endpoints within one year of anticoagulant initiation. Results: The average number of potential drug interactions per patient was higher for warfarin than others (3.04 vs. 1.28 (apixaban), 1.02 (rivaroxaban), and 0.98 (LMWH)). The severity of the interactions based on grade was, for apixaban: 1.6% grade X, 50.8% grade D, and 47.5% grade C; for rivaroxaban: 2.1% grade X, 64.9% grade D, 33.0% grade C; for LMWH, 0% grade X, 66.7% grade D, 33.3% grade C; and for warfarin, 0% grade X, 29.4% grade D, 70.6% grade C. At the end of the investigational period, 11 bleeds and 7 VTEs were reported. Drug combinations significantly associated with an increased bleeding risk were crizotinib with apixaban or rivaroxaban and PPIs with warfarin. The use of sulfamethoxazole-trimethoprim with warfarin was associated with an increased VTE risk. Conclusions: DOACs had fewer DDIs than warfarin, although interaction severity differed between anticoagulants. Some anticoagulant-drug interactions were associated with bleeding or VTE. Although not powered for analysis, DDI severity did not affect bleeding rates and inversely correlated with VTE risk.